Kesulitan Peserta Didik dalam Pembelajaran Matematika Materi Perkalian dan Pembagian di Sekolah Dasar - Sihombing, Jesika Merdisinta; Syahrial, Syahrial; Manurung, Usy Sarah (Jurnal Didaktika Pendidikan Dasar, 2023)
This research aims to determine students’ difficulties in learning mathematics, multiplication and division material in elementary school. The method used is the literature study method. The research subjects are articles and books related to the research topic. The results of this research show that students’ difficulties in learning mathematics on multiplication and division in elementary school are caused by a lack of student motivation to learn, using the wrong process, not being careful, not having memorized multiplication and division, feeling bored when learning multiplication and division, not knowing the first steps in working on questions. mathematics stories, not focusing when learning, and misconceptions about multiplication and division. The difficulties faced by students are difficulties in calculations, understanding concepts, differences in place value, differences in arithmetic operation symbols, and understanding mathematical story problems. The solution to overcome these difficulties is that teachers require students to memorize multiplication 15 minutes before starting learning, use singing methods, use mathematics, use fun learning models, and motivate students to increase their interest in learning in class. Parents at home are expected to guide and help children in completing their assignments.